Corporate Governance dan Kepercayaan Investor Peran Moderasi Going Concern, Corporate Reporting, dan Covid-19 - Muhammad , Ghazi; zaitul; Ilona, Desi (Cattleya Darmaya Fortuna, 2024)
The study's objective is to empirically test the influence of corporate Governance on investor confidence: going concerns, corporate reporting, and covid-19 as moderating variables using four control variables: company size, leverage, company age and profitability. The companies operating in the sub-sector of financing services listed in the Indonesia Stock Exchange from 2018 to 2023. The final sample is fifteen companies. The secondary data obtained from www.idx.co.id and the company's official website is the research data type. Data is analysed using moderated regression using SPSS and Gretl. The empirical finding is that corporate Governance and going concerns positively influence investor confidence, whereas corporate reporting and COVID-19 have no relationship with investor confidence. Going concerns moderate the relationship between corporate Governance and investor confidence, while corporate reporting and COVID-19 do not moderate the relationship between Corporate Governance and investor confidence.